Gendered migrant experiences and multiple identities of Muslim women in Leila Aboulela’s Minaret and Shelina Janmohamed’s Love in a Headscarf - Hasan, Md. Mahmudul (2013)
Traditional Muslim societies are internally pluralistic containing multiple groups with different conceptions of Islam and hence may not be construed as monolithic and static. However, when Muslims migrate to the West in order to settle down there, they encounter a different mode of plurality and possibility. While immigrant Muslim men are racked with somewhat unacknowledged exilic anxieties, the challenge and possibility of Muslim women largely concern gender and religion. For a group of Muslim women, the West facilitates a critical interrogation of their feeling of identity vacillation and creates a useful framework for thinking about their religious observances, which eventually helps them regain their somewhat lost identity. For many others, it provides a third space in which they can confidently engage in a reinterpretation of the Islamic texts and thus reclaim an identity which liberates them from the culturally enacted practices of their country of origin. Based on these theoretical premises, my paper will analyze the representation of diasporic Muslim women and their multiple identities in Leila Aboulela’s Minaret (2005) and Shelina Janmohamed’s Love in a Headscarf (2009). It will contextualize these two texts and show how, face to face with possibilities and pitfalls, Muslim women negotiate and prioritize Islamic identity in the metropolis.